Strategies for Increasing Buffalo Productivity through Improvement in Feed and Genetic - Chalid Talib; Tati Herawati; Hastono . (Indonesian Center for Animal Research and Development, 2014)
Buffalo is indigenous livestock of Asia, classified as beef buffaloes that evolve in Southeast Asia and China and dairy buffaloes exist in Indo-Pakistan and Mediteranian. In Indonesia, beef buffaloes are known as swamp buffalo and there are seven new buffalo breeds namely Pampangan, Sumbawa, Moa, Toraya, Simelue, East Kalimantan and South Kalimantan. Buffaloes are reared in extensive traditional system characterized by low growth rate and reproduction ability due to feed shortage and high inbreeding rate. Feed improvements in female is required to get dry matter intake 2.5-2.7% of body weight (BW) that consist of 70% roughage and 30% concentrates, will show a clear sign of estrus. In the male when feed consumption is 2.7-3.5% of BW; it will perform growth rate of 0.6 kg/head/day. Genetic improvement is conducted through selection based on BW in certain ages, reproduction ability and parents without recessive alleles. Distribution of proven bulls and their sperm in outbreeding system would improve the production and reproduction performance, reduce inbreeding level and increase breeding farmer’s income. It is expected that in the long term, the population of buffaloes in Indonesia will increase. Key words: Buffalo, strategies, feed, genetic